α4/α9 Integrins Coordinate Epithelial Cell Migration Through Local Suppression of MAP Kinase Signaling Pathways - Hight-Warburton, Willow; Felix, Robert; Burton, Andrew; Maple, Hannah; Chegkazi, Magda S.; Steiner, Roberto A.; McGrath, John A.; Parsons, Maddy (Frontiers in Cell and Developmental Biology, 2021)
Adhesion of basal keratinocytes to the underlying extracellular matrix (ECM) plays a key role in the control of skin homeostasis and response to injury. Integrin receptors indirectly link the ECM to the cell cytoskeleton through large protein complexes called focal adhesions (FA). FA also function as intracellular biochemical signaling platforms to enable cells to respond to changing extracellular cues. The α4β1 and α9β1 integrins are both expressed in basal keratinocytes, share some common ECM ligands, and have been shown to promote wound healing in vitro and in vivo. However, their roles in maintaining epidermal homeostasis and relative contributions to pathological processes in the skin remain unclear. We found that α4β1 and α9β1 occupied distinct regions in monolayers of a basal keratinocyte cell line (NEB-1). During collective cell migration (CCM), α4 and α9 integrins co-localized along the leading edge. Pharmacological inhibition of α4β1 and α9β1 integrins increased keratinocyte proliferation and induced a dramatic change in cytoskeletal remodeling and FA rearrangement, detrimentally affecting CCM. Further analysis revealed that α4β1/α9β1 integrins suppress extracellular signal-regulated kinase (ERK1/2) activity to control migration through the regulation of downstream kinases including Mitogen and Stress Activated Kinase 1 (MSK1). This work demonstrates the roles of α4β1 and α9β1 in regulating migration in response to damage cues.